DETERMINATION OF DISEASE SEVERITY AND INFLAMMATORY BIOMARKERS NAMELY C-REACTIVE PROTEIN TO ALBUMIN RATIO AND FIBRINOGEN TO ALBUMIN RATIO AMONG PATIENTS WITH COMMUNITY ACQUIRED PNEUMONIA AT A TERTIARY HEALTHCARE FACILITY IN ETAWAH DISTRICT: A CROSS SECTIONAL STUDY - Dr Adesh Kumar; Dr Ashish Kumar Gupta; Dr Aditya Kumar Gautam; Dr. Naresh Pal Singh; Dr Prashant Yadav; Dr. Dhiresh Chourasiya; Dr Gauri Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: To determine disease severity and inflammatory biomarkers namely C-Reactive Protein to Albumin ratio and Fibrinogen to Albumin ratio among patients with Community Acquired Pneumonia.Material and Method: In this observational cross-sectional study the CURB-65 score was used to assess the severity of CAP at the time of admission, after which patients were divided into three groups based on their scores: the low-risk CAP group (scores 0-1), the moderate-risk CAP group (score 2), and the severe CAP group (scores 3-5), CAR and FAR scores were calculated and severity determined and compared with CURB 65. Result: Total 152 patients were analyzed that nearly half (49.3%) were between 40 and 69 years old. The second-largest group was those aged 70 and above (21.7%), followed by patients aged 25-39 years (20.4%), and those under 25 years (8.6%).  Males (66.4%) were more compared to females (33.6%). CURB-65 severity scores showed 48% of patients had a severity score of 1, 37.5% had a score of 2, and 8.6% had severe pneumonia with scores of 3-5. Higher CAR values were observed in severe cases (mean 77.4±57.6) compared to non-severe low-risk (28.4±25.2) and non-severe moderate-risk (46.4±26.4) groups. Similarly, FAR was significantly higher in severe cases (mean 246.3±130.8) compared to non-severe groups (174.1±75.5 and 204.2±87.7, respectively). Conclusion: Elevated biomarkers such as C-reactive protein (CRP) (p